The relationship between person perceived of fit and work engagement - Nurnajmi, Rosli (2015)
This study examines the direct relationship between person-job fit, person organization fit, person-group fit, person-supervisor fit and work engagement. A total of 500 questionnaires were disributed to respondents who had agreed to participate in this study. At the end of the survey period, 140 questionnaire were returned, yielding a return rate of 28%. However, only data from 137 respondents are usable for further analyses. Hypotheses for direct effect were tested using multiple regression analyses. Results showed that only person-supervisor fit was significantly positively associated with work engagement. Implications of the findings, potential limitations, and directions for future research are discussed